RISK FACTORS STUNTING INCIDENCE IN CHILDREN AGED 6-36 MONTHS IN JEMBER REGENCY - Ninna Rohmawati (UNEJ e-Proceeding, 2017)
Background: Period toddlers are vulnerable malnourished. One of the nutritional problems that are often encountered in toddlers is stunting. Stunting in children under five is an indicator of nutritional status that can give you an idea disruption overall socio-economic situation in the past. Based on the results Riskesdas 2013 the prevalence of stunting in children under five years of 37.2% Indonesia. There are various factors related to the occurrence of stunting. This study aims to know risk factors associated with the incidence of stunting among children aged 6-36 months in the district of Jember. Methods: This research is an observational research with quantitative methods and using cross-sectional design. The research sample was 120 toddlers in Kalisat districts of Jember regency that met the inclusion criteria. The data obtained and in the bivariate analysis using chi-square then continued right with multivariate analysis by using logistic regression. Results: The results showed that stunting children come from families who have parents with lower education and income family, parenting and poor diet, and not given breast milk exclusive, never suffered an infection, have parents were classified as short. Conclusions: The most dominant risk factors on the incidence of stunting that family income and father's height. Keywords: stunting, family income, father's height.